2019
DOI: 10.1002/ajpa.23885
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional geometric morphometric analysis of the distal radius insertion sites of the palmar radiocarpal ligaments in hominoid primates

Abstract: Objectives: To identify anatomic differences in the insertion sites of the palmar radiocarpal ligaments in different species of hominoid primates that may be related to their different types of locomotion. Materials and methods:We have used three-dimensional geometric morphometrics (3D GM) to analyze the distal radius ligament insertion sites in 31 Homo sapiens, 25 Pan troglodytes, 31 Gorilla gorilla, and 15 Pongo pygmaeus. We have also dissected the radioscaphocapitate (RSC), long radiolunate (LRL) and short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…This indicates that when comparing either gorillas and humans or chimpanzees and humans, FR in PP2–4 may act as functional markers by separating African apes from humans. This is in keeping with Drapeau (2008) and Casado et al (2019) who found that entheses in limbs do indicate functional differences between African apes and humans. Interestingly, although previous research shows that body size is a significant predictor of insertion site variability (e.g., Nolte & Wilczak, 2013; Zumwalt, 2006) and our results suggested that body size exerts an influence on FR (Figure 3 and Table 4), this cannot explain differences in FR when comparing humans to chimpanzees.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This indicates that when comparing either gorillas and humans or chimpanzees and humans, FR in PP2–4 may act as functional markers by separating African apes from humans. This is in keeping with Drapeau (2008) and Casado et al (2019) who found that entheses in limbs do indicate functional differences between African apes and humans. Interestingly, although previous research shows that body size is a significant predictor of insertion site variability (e.g., Nolte & Wilczak, 2013; Zumwalt, 2006) and our results suggested that body size exerts an influence on FR (Figure 3 and Table 4), this cannot explain differences in FR when comparing humans to chimpanzees.…”
Section: Discussionsupporting
confidence: 89%
“…If entheses signal behavior, the higher forces African apes apply on their hands should leave larger insertion sites than in humans. This may help to elucidate the suitability of entheses to inform on the use of the hands in taxa with unknown activity patterns (e.g., human past populations), yet this kind of study is relatively scarce (Casado et al, 2019; Drapeau, 2008; Milella, 2014; Rabey et al, 2015; Zumwalt, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The landmarks previously proposed by Casado et al [38] were used to represent the morphology of the two insertion sites of the palmar radiocarpal ligaments in the distal radial epiphysis. Nine Type II and one Type III landmarks were used: the L1-L4 landmarks for the SRL insertion site and the L5-L10 landmarks for the common insertion site of the RSC and LRL (Figure 1).…”
Section: D Gm Analysismentioning
confidence: 99%
“…We found that the morphology of these two insertion sites was related to the type of locomotion used by each of the species. The insertion sites in the more arboreal species, like Pongo pygmaeus, are larger, with a palmar orientation of the SRL ligament insertion site, while those of the knuckle-walkers (Gorilla gorilla) are smaller, with an ulnopalmar orientation of the SRL ligament insertion site, presenting Pan troglodytes an intermediate position [38]. This relationship between the morphology of a ligament insertion site and type of locomotion has also been observed in other anatomical regions of hominoid primates, such as the insertion sites of the ligaments holding the flexor digitorum profundus and superficialis muscles in proximal phalanges [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation